Postales Digitales de Ilustración Científica para el rescate de la fauna emblemática del Ecuador. - Cevallos Cevallos, Joshua David (2025)
The purpose of this research project is to design digital postcards of scientific illustration as educational and informative material that will contain the most outstanding and important characteristics of the species, a good composition, attractive design and eye-catching presentation to highlight the emblematic fauna, promoting awareness and appreciation for the unique biodiversity of Ecuador. The starting point of the project will be research about specific species that have a considerable biological-ecological and cultural weight or importance, in addition to that, important data will be collected about the emblematic species that will be placed in the final digital postcards. The research will also include the importance and weight of scientific illustration as a style of illustration to represent the emblematic species that will be part of the theoretical framework of the project. On the other hand, professionals in the areas of graphic design, illustration and biology will be consulted through interviews so that the project has a better direction and the digital postcards meet the criteria of quality and professionalism with which any thesis project should be carried out. Both traditional and digital illustration techniques will be indispensable to produce scientific illustrations of each of the species